2021
DOI: 10.1016/j.parepi.2021.e00206
|View full text |Cite
|
Sign up to set email alerts
|

Reemergence of zoonotic cutaneous leishmaniasis in an endemic focus, northeastern Iran

Abstract: Zoonotic cutaneous leishmaniasis (ZCL) is a form of disease, which is mostly caused by Leishmania major (L.major ) in the Old World with high incidence through early life. Recently, the high incidence of CL has been reported in Jajarm County, northeastern Iran. The aim of the present study was to investigate the epidemiological aspects of CL and to identify Leishmania spp. in the area. Between 2012 and 2018, patients with active lesions suspected of CL were examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Our results are consistent with those of other studies showing that LC lesions in L. major are located in the upper and lower limbs, unlike those in L. tropica. Indeed, studies in Ecuador and Tunisia have shown that LC lesions caused by L. tropica are mainly located on the face and then on the upper limbs, while those caused by L. major are preferentially located on the upper and lower limbs [13,14]. This can be attributed to the sandfly vectors of L. major CL: Phlebotomus papatsi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are consistent with those of other studies showing that LC lesions in L. major are located in the upper and lower limbs, unlike those in L. tropica. Indeed, studies in Ecuador and Tunisia have shown that LC lesions caused by L. tropica are mainly located on the face and then on the upper limbs, while those caused by L. major are preferentially located on the upper and lower limbs [13,14]. This can be attributed to the sandfly vectors of L. major CL: Phlebotomus papatsi.…”
Section: Discussionmentioning
confidence: 99%
“…This can be attributed to the sandfly vectors of L. major CL: Phlebotomus papatsi. In addition, the force of transmission of this form, which is considered more important, leads to a greater risk of suffering several infectious bites at different sites over a short period before the establishment of a protective immune response [13,15].…”
Section: Discussionmentioning
confidence: 99%
“…Other factors affecting the incidence or spread of cutaneous leishmaniasis (ZCL); consist of atmospheric factors such as rainfall, temperature, sunshine, and humidity, males and those aged <10 years, and The emergence of the Coronavirus Disease 2019 (COVID-19) pandemic in Fars province (101). climatic factors in Kerman province (1), age groups in Ilam province (18), and seven criteria, including mean temperature, mean humidity, mean rainfall, elevation, distance from river, land use, and soil texture.…”
Section: Introductionmentioning
confidence: 99%
“…,49,55,63,72,98-100,122 . ) Other factors affecting the incidence or spread of cutaneous leishmaniasis (ZCL); consist of atmospheric factors such as rainfall, temperature, sunshine, and humidity, males and those aged <10 years, and The emergence of the Coronavirus Disease 2019 (COVID-19) pandemic in Fars province(101 ). climatic factors in Kerman province (1).…”
mentioning
confidence: 99%
“…In 2020, more than 85% of the cases belonged to 10 countries including Iran, where about 20,000 new cases occur per year (2). Two different forms of CL including zoonotic cutaneous leishmaniasis (ZCL) and anthroponotic cutaneous leishmaniasis (ACL) occur in Iran (3). The causative agent of ZCL which is observed in the rural area is Leishmania major (L. major) while ACL is related to urban areas and caused by Leishmania tropica (L. tropica) (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%